,,Rettungsprogramme“ für Krisenländer verschärften die Krise — eine Replik - Ernst Niemeier (Wirtschaftsdienst, 2016)
In der Augustausgabe 2015 veröffentlichte der Wirtschaftsdienst einen Aufsatz von Jens Boysen-Hogrefe und Ulrich Stolzenburg über ,,Rettungsprogramme und ,Ownership ` — Irland, Portugal und Griechenland im Vergleich“. Nach der Replik von Ernst Niemeier folgt hierzu eine Erwiderung der Autoren. – – In his reply, Niemeier accuses Boysen Hogrefe and Stolzenburg of erroneously ascribing the failing of the Greek programme to insufficient "ownership", whereas the true cause is - in his view - an inadequate austerity policy. The alleged success of this policy in Portugal and Ireland refers solely to GDP growth and ignores the continuing high levels of unemployment in those countries. Boysen- Hogrefe and Stolzenburg insist that the "success" of a rescue programme actually implies that the respective country is able to return to capital markets. The Greek crisis was structural rather than cyclical, so a temporary stabilisation of domestic demand (financed by additional foreign debt) would not have solved the issue.
Keywords: E65; F34; F53; 330